Auditor Industry Specialization as a Moderator of the Relationship Between Fair Value Measurement of Non-Current Assets and Audit Quality: Evidence from Indonesian Listed Companies - Jesica Ramadanty; Hasni Yusrianti; Yulia Saftiana (International Journal Multidisciplinary Science, 2026)
This study investigates the effect of fair value measurement of non-current assets on audit quality and examines whether auditor industry specialization moderates this relationship. Using a quantitative research design, the study analyzes panel data from 152 companies listed on the Indonesia Stock Exchange over the 2022–2024 period, resulting in 456 firm-year observations. The hypotheses are tested using panel data regression analysis. The results provide evidence that fair value measurement of non-current assets negatively affects audit quality at a statistically significant level. Increased reliance on fair value measurement introduces greater estimation uncertainty and audit complexity, which may impair auditors' ability to maintain high audit quality. Auditor industry specialization does not significantly moderate this relationship, indicating that industry-specific expertise alone is insufficient to mitigate the challenges associated with auditing complex fair value estimates.